Social Forces Sustaining the Israeli-Palestinian Tensions: A Dynamical Psychology Perspective - Michaels, Jay Lawrence (International journal of conflict and violence, 2017)
The Israeli-Palestinian conflict remains one of the most deeply entrenched in the world. While there is great knowledge about numerous individual factors contributing to this conflict’s persistence, much of the information is fragmented and segregated into different disciplines. This article seeks to integrate an array of literature using a dynamic systems perspective to examine how social – as opposed to political – forces contribute to ongoing tensions. The first part describes the dynamical systems perspective, focusing on how intractable conflicts emerge as a result of interlinking factors that anchor the social system in patterns that resist change. The second part explores the Israeli-Palestinian conflict in terms of specific social forces contributing to the conflict’s persistence. These include leadership issues, economic inequalities poverty, youth disenfranchisement, and population distribution. Then the contribution maps how the discussed social factors interrelate to reinforce the ongoing tensions and addresses how small-scale approaches may circumvent the volatile, entrenched patterns of hostility